IDENTIFYING PATTERNS OF TOBACCO USE IN MIDDLE AND HIGH SCHOOL STUDENTS IN THE DOMINICAN REPUBLIC: A LATENT CLASS ANALYSIS - César Arredondo Abreu; Kari-Lyn Sakuma (Instituto Tecnológico de Santo Domingo (INTEC), 2024)
The Dominican Republic (DR) has minimal national tobacco control strategies for youth tobacco use. This study seeks to understand how different patterns of tobacco use might occur in groups of Dominican youth. Methods: Using Latent Class Analyses, we analyzed the DR's 2016 Global Youth Tobacco Survey dataset (N= 1,532), a nationally representative school-based survey. We examined two indicators (ever use, past 30-day use) of cigarettes, shishas, smokeless tobacco, and e-cigarettes. Multinomial logistic regression was used to analyze predictors of class membership. Results: Five subclasses of tobacco users were identified: non-users (58.44%), shisha experimenters (18.55%), poly-tobacco experimenters (10.66%), poly-tobacco users (8.57%), and smokeless tobacco with experimentation (3.79%). Compared to non-users, Shisha experimenters had higher odds of being male, having more spending money, and having observed someone smoking tobacco in their house. Poly-tobacco experimenters and Poly-tobacco users class had higher odds of having observed someone smoking tobacco in their house. Smokeless tobacco, with experimentation of other forms of tobacco, had higher odds of having observed someone smoking tobacco in their house and outside. Discussion: Our findings indicate that most tobacco users belong to the shisha experimenters or were multiple product experimenters/user classes. This suggests that tobacco control strategies should focus on multiple products and aim prevention efforts toward younger male students.